Analysis Of The Influence Of Employee Welfare And Social Gap On Loyalty Professional - Zuriani Ritongan Ritongan; Chairul bariah; Nurjannah Nurjannah; Hayanuddin Hayanuddin (Institute of Computer Science (IOCS), 2022)
PT. XXX is a companyplantations that are managed professionally so that employees who are truly able to work optimally and optimally are needed to increase the company's ability to compete in this globalization era. One of the most important factors is the employee factor. Improving the quality of human resources is inseparable from increasing employee loyalty to the work they do. To support job loyalty, one of the factors is the level of employee welfare. With the existence of employee welfare, it is hoped that job professionalism can be achieved. Based on the description above, the writer feels interested in conducting a thesis research entitled: